Optimized design of a Linear Fresnel reflector for solar process heat applications - Pulido Iparraguirre, Diego; Valenzuela Gutiérrez, Loreto; Serrano Aguilera, Juan José; Fernández García, Aránzazu (Elsevier, 2019)
Heat demands in industrial processes represent a high rate of the thermal energy consumption that could be directly delivered by a concentrated solar thermal technology. Linear Fresnel reflectors are a promising example of this kind of technology. This paper presents an innovative and optically optimized design of linear Fresnel collector for solar process heat applications. An in-house ray trace code was employed to evaluate different geometrical options of the solar collector over conventional concepts, aiming to maximize its optical performance and tackle the inherent weakness of this concentrating solar technology when it is compared to other type of concentrators. Geometrical modifications accomplished in the optimization process include the tilt of the concentrator and receiver, the receiver displacement and the concentrator rotation along with the optimization of other relevant parameters. As a result, a significant upgrade of the monthly power on the receiver was achieved, with an average enhancement ranging from 2% to 61%, compared to a standard linear Fresnel collector without the proposed modifications. This result provides a more homogenous thermal power profile delivered along the year, which is an important requirement to place the technology in the spotlight.
Keywords: Energía térmica solar; Concentrating solar thermal technology; Linear Fresnel reflector; Ray trace code; Optimized optical performance; Incidence angle